A comparison of sympathetic outflow to muscles between cervical spondylotic amyotrophy and ALS - Shindo, Kazumasa; Watanabe, Harue; Tanaka, Haruyuki; Nagasaka, Takamura; Tsunoda, Shin-ichi; Shiozawa, Zenji (Amyotrophic Lateral Sclerosis and Other Motor Neuron Disorders, 2002)
To confirm the diagnostic usefulness of muscle sympathetic nerve activity (MSNA) in differentiation between cervical spondylotic amyotrophy (CSA) and amyotrophic lateral sclerosis (ALS) with cervical spondylosis (CS), MSNA, heart rate (HR) and blood pressure (BP) were recorded in 10 patients with CSA and ALS with CS, and age-matched healthy volunteers at rest and during head-up tilting. There were no differences in age, disability scores, pulmonary function, and HR or BP at rest between ALS and CSA groups. Resting MSNA was significantly greater in patients with ALS with CS than in comparison groups (P<0.001) with virtually no overlap between ALS and the CSA groups. During head-up tilting, changes in BP and MSNA were significantly less in patients with ALS than in patients with other subjects. MSNA at rest clearly differentiated CSA from ALS with CS, suggesting diagnostic utility.